Barsilowsky's base and Perkin's base: two products from the oxidation of p-toluidine. (1st June 2014) - Plater, M. John; Harrison, William
The oxidation of p-toluidine in H+/H2O can give mainly a tetramer, a trimer, or a mixture of both. The outcome is dependent upon the oxidant, the pH and the concentration ofp-toluidine. Both the trimer and tetramer are definitively characterised by X-ray single crystal structure determination.